Should Contractual Clauses that Forbid Renegotiation Always be Enforced? - Patrick W. Schmitz (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
Recent work in the field of mechanism design has led some researchers to propose institutional changes that would permit parties to enter into nonmodifiable contracts, which is not possible under current contract law. This paper demonstrates that it may well be socially desirable not to enforce contractual terms that explicitly prevent renegotiation, even if rational and symmetrically informed parties have deliberately signed such a contract. The impossibility to prevent renegotiation can constrain the principal's abilities to introduce distortions in order to reduce the agent's rent, so that the first-best benchmark solution will more often be attained.
Keywords: K12; 330; Contract modification; Renegotiation; Moral hazard; Vertragstheorie; Vertragsrecht; Moral Hazard; Theorie